Critical Assessment of Master Plan in Bilaspur City andIts Effectiveness(1976-2031) - Bera, Dipankar; Das, Jadab; Chatterjee, Debrupa; Kuity, D. P. (International Journal of Psychosocial Rehabilitation, 2019)
The master plan of any city plays an important role in the development of class I cities in India. The three master plans taken on Bilaspur city of Chhattisgarh from 1976 to 2016 have been discussed to show how they have become successful master plans. The study is based on a critical analysis of the proposed and existing master plan of Bilaspur City. And it follows the rate of implementation to suggest a viable scheme for future development. To know the actual causes of variation rate and its effectiveness in Master Plan. The master plan of Bilaspur city is compared with the master plan of Chandigarh city. The study has been conducted based on the secondary data collection from various master plans published by the Directorate of Town and Country Planning Organization, Bilaspur (1976, 2001, and 2016). In this research work, several statistical tools have been used, like work participation ratio, land utilization rate, and rate of plan effectiveness, to analyse the land use of Bilaspur city. It is verified whether the existing master plan is well recognized or not. The comparison of land use data for the years 1956 and 1976 revealed that 124 percent had extended the urban area during 20 years. The land utilization rate per 1000 persons was 7.20 hectares and 6.5 hectares, respectively, for 1956 and 1976. The land utilization rate was 4.84 & 25.59 hectares per 1000 population in 2001 and 2011 Census. Population densities of area were 20,645 and 5,380 per sq. km. in the 2001 & 2011 Census. The rate of effectiveness in a master plan in 2001 was 53.08 and 120.99 percent in 2011. If policymakers plan for a short-term duration every 5 to 10 years, it will accelerate funding and adopt new technology for sustainable urban development. If the unplanned areas of the city are newly added to the master plan, then the inequality of development will be eliminated and it will be fruitful for the development of the city. If the review committee has been formed for the field work, the committee will supervise and maintain land utilization.